1997
DOI: 10.1088/0953-2048/10/1/010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Sn substitution in the superconducting system

Abstract: We studied the effect of Sn substitution in a new mercury-based superconductor with nominal composition . At this stage of investigation the material is multiphasic with dominating superconducting phases up to x = 0.3. It was established that Sn stimulates the formation of the Hg-1212 phase and enhances the diamagnetic volume fraction but also the weak-link behaviour. Together with the SEM - EDS analysis, the shift of some of the XRD peaks, as well as the gradual decrease of with the dopant content x, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Due to these, the as synthesized Hg-12(n-1)n phases are not so stable as the other HTSC phases of cuprate oxide family. Many attempts to overcome these problems have been made, but they have only limited success [5][6][7]. It is now known that partial replacement of Hg +2 in oxygen deficient HgO δ layer by cations having higher oxidation states than Hg +2 e.g.Tl +3 , Sn +4 , Bi +3 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these, the as synthesized Hg-12(n-1)n phases are not so stable as the other HTSC phases of cuprate oxide family. Many attempts to overcome these problems have been made, but they have only limited success [5][6][7]. It is now known that partial replacement of Hg +2 in oxygen deficient HgO δ layer by cations having higher oxidation states than Hg +2 e.g.Tl +3 , Sn +4 , Bi +3 etc.…”
Section: Introductionmentioning
confidence: 99%
“…It was established that the x 0.1 samples are not superconducting. This is not observed in other Sn-containing superconducting systems, where SC exists up to x 0.3 [9,[11][12][13][14]. Therefore the Sn-doping more rapidly destroys the SC in Ru-1222 than in conventional superconductors.…”
Section: Resultsmentioning
confidence: 89%
“…It was also shown that the Sn-doping favors the melt-texture-growth (MTG) of YBaCuO [10]. The authors of [11,12] studied the effect of Sn-substitution on the superconducting properties of the Hg-1223 and (Pb, Cu)-1212 systems. It was established that Sn stimulates the Hg-1212 phase formation and enhances both the diamagnetic volume fraction and the weak link behavior.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12] Sn doping resulted in a significant enhancement of J c for more highly doped samples. [13][14][15] Sn ions in the 4 + valence state dominantly occupy Cu sites.…”
Section: Introductionmentioning
confidence: 99%